PENGUKURAN INDEKS RESILIENSI MASYARAKAT TERHADAP BENCANA GEMPA BUMI DI KABUPATEN KLATEN - Lian Yuanita Andikasari; Ashar Saputra; Fikri Faris (Jurnal Manajemen Bencana (JMB), 2023)
Klaten Regency is one of the areas affected by the 2006 Yogyakarta earthquake disaster. Several sub-districts experienced the impact of this disaster, including Wedi Sub-District, Gantiwarno Sub-District, and Prambanan Sub-District. The earthquake caused casualties and damage in Klaten Regency. An earthquake disaster is a disaster that can occur at any time, so there is a need for community preparedness in facing disasters by knowing community resilience. This research aims to measure the community resilience index of the three sub-districts in facing earthquake disasters. This research was conducted on 359 respondents, namely 144 respondents in Wedi Sub-District, 103 respondents in Gantiwarno Sub-District, and 112 respondents in Prambanan Sub-District. Respondents filled out the questionnaire by looking at 4 (four) aspects, namely social aspects, economic aspects, institutional or institutional aspects and physical aspects. Data analysis uses the Guttman scale and there are 5 (five) categories of resilience index levels, namely very low, low, moderate, high, very high. The calculation results show that the Wedi Sub-District resilience index value is 1.18; Gantiwarno Sub-District was 1.16; Prambanan Sub-District is 1.11 and the three sub-districts are in the moderate category.